2008
DOI: 10.1016/j.jcmg.2008.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence Between the 17-Segment Model and Coronary Arterial Anatomy Using Contrast-Enhanced Cardiac Magnetic Resonance Imaging

Abstract: Four segments were completely specific for left anterior descending artery occlusion. No segment can be exclusively attributed to the right coronary artery or LCX occlusion. However, analysis of adjacent segments increased the specificity for a given coronary occlusion. These findings bring objective evidence in the appropriate segmentation of coronary arterial perfusion territories and assist accurate assignment of the culprit vessel in various imaging modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(102 citation statements)
references
References 21 publications
5
93
1
3
Order By: Relevance
“…Pereztol-Valdés et al analyzed the correspondence of the 17 LV segments with each of the three major epicardial coronary arteries by myocardial perfusion single-photon emission CT (SPECT) studies during elective percutaneous coronary intervention (PCI) in 50 patients. 95 The study showed that the most specific segments (anterior, anteroseptal, and all apical segments except the inferoseptal) corresponded to the LAD, and the basal anterolateral segment (segment 6) to the LCx, while no segment could be exclusively attributed to the RCA. Eight segments were not attributed to a single coronary artery.…”
Section: Correspondence Between Left Ventricular 17 Myocardial Segmenmentioning
confidence: 89%
See 2 more Smart Citations
“…Pereztol-Valdés et al analyzed the correspondence of the 17 LV segments with each of the three major epicardial coronary arteries by myocardial perfusion single-photon emission CT (SPECT) studies during elective percutaneous coronary intervention (PCI) in 50 patients. 95 The study showed that the most specific segments (anterior, anteroseptal, and all apical segments except the inferoseptal) corresponded to the LAD, and the basal anterolateral segment (segment 6) to the LCx, while no segment could be exclusively attributed to the RCA. Eight segments were not attributed to a single coronary artery.…”
Section: Correspondence Between Left Ventricular 17 Myocardial Segmenmentioning
confidence: 89%
“…In the working group paper, the inferior segments (4, 10, and 15) were attributed to the RCA, but in the study by Pereztol-Valdés et al, all patients with LCx disease had involvement of the inferior segments. 95 These observations most probably reflect the great variability in blood supply to the inferior and lateral wall.…”
Section: Correspondence Between Left Ventricular 17 Myocardial Segmenmentioning
confidence: 99%
See 1 more Smart Citation
“…For right coronary artery or left circumflex artery occlusions, no segments were 100% specific. 26 Lund et al demonstrated that delayed enhanced MRI had a higher sensitivity compared to SPECT. 27 DE-MRI presents a sensitivity of 99% in measuring the extent of the infarction scar and 94% in measuring transmural enhancement.…”
Section: Assessment Of Myocardial Viabilitymentioning
confidence: 99%
“…However, the AHA noted that the name of the segments should define the location relative to the long axis of the heart and the circumferential location, and individual myocardial segments can be assigned to the three major coronaries by considering their anatomic variabilities (2) . In addition, contrary to the conventional 17‐segment model, several studies have reported, using single‐photon emission computed tomography (SPECT), cardiac magnetic resonance (CMR), and CT, that there are variations in the mapping of segments to left ventricular territories, due to their anatomic variations 3 , 4 , 5 . Therefore, they proposed a revised mapping of segments considering anatomic variations, where some segments were assigned to multiple territories due to per‐patient variability.…”
Section: Introductionmentioning
confidence: 99%